PENGEMBANGAN VIDEO PEMBELAJARAN MENULIS PUISI BARU SISWA KELAS V SEKOLAH DASAR - Karta, I Made; -, Sudaryono; Budiyono, Herman (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2012)
This article is based on a developmental research wich is aimed at constructing video learning to assist modern poetry writing. The video is developed by using the contextual approach. The model development employs the Borg and Gall’s model (2003). Based on data analysis of the development process, experts validation, and field trials of the product, it can be concluded that the quality of video learning is good in assisting writing modern poetry process. Therefore, it is suggested that the media can be used a media in teaching modern poetry for elementry school students. Kata kunci: video learning, new poetry